LO045: Sonography in Hypotension and Cardiac Arrest (SHoC) - Cardiac Arrest: A consensus on the integration of point of care ultrasound into advanced cardiac life support during cardiac arrest. (2nd June 2016) - Atkinson, P.; Bowra, J.; Milne, J.; Lambert, M.; Jarman, B.; Noble, V.; Lamprecht, H.; Lewis, D.; Harris, T.; Gangahar, R.; Bomann, S.; Goudie, A.; et al.
Abstract : Introduction: Point of care ultrasound (PoCUS) provides invaluable information during resuscitation efforts in cardiac arrest by determining presence/absence of cardiac activity and identifying reversible causes such as pericardial tamponade. There is no agreed guideline on how to safely and effectively incorporate PoCUS into the advanced cardiac life support (ACLS) algorithm. We consider that a consensus-based priority checklist using a "4 F's" approach (Fluid; Form; Function; Filling), would provide a better algorithm during ACLS.Methods: The ultrasound subcommittee of the Australasian College for Emergency Medicine (ACEM) drafted a checklist incorporating PoCUS into the ACLS algorithm. This was further developed using the input of 24 international experts associated with five professional organizations led by the International Federation of Emergency Medicine. A modified Delphi tool was developed to reach an international consensus on how to integrate ultrasound into cardiac arrest algorithms for emergency department patients.Results: Consensus was reached following 3 rounds. The agreed protocol focuses on the timing of PoCUS as well as the specific clinical questions.Core cardiac windows performed during the rhythm check pause in chest compressions are the sub-xiphoid and parasternal cardiac views. Either view should be used to detect pericardial fluid, as well as examining ventricular form (e.g. right heart strain) and function, (e.g. asystole versus organized cardiac activity).Supplementary views include lung views (for absent lung sliding in pneumothorax and for pleural fluid), and IVC views for filling .Additional ultrasound applications are for endotracheal tube confirmation, proximal leg veins for DVT, or for sources of blood loss (AAA, peritoneal/pelvic fluid).Conclusion: The authors hope that this process will lead to a consensus-based SHoC-cardiac arrest guideline on incorporating PoCUS into the ACLS algorithm.